IMPLEMENTASI MOBILE AUGMENTED REALITY 3 DIMENSI PADA PETUNJUK PRAKTIKUM DRIVE TEST - Alfin Hikmaturokhman; Satrio Adi Wiguna; Elisa Usada (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2015)
Nowaday technology has been growing up in. One of them is cellular technology, the increasing of mobile technology requires the better service. To overcome these problem, the operator have to do Drive Test to identify and analyz the network quality of service, to improve the learning activities about Drive Test then needed an option for it. It can be overcome by the module Drive Test lab manual with applications that can support the user with an attractive visual display. The application materials will be designed on the basis of such a simulation about Drive Test Handover process, the process occurs as a result of Drop Call or constraints of a mobile network that frequently appear on the user's mobile phone, and the basic steps Drive Test. This lab manual application modules is created using a mobile Augmented Reality technology. The method which is used for the development of systems using waterfall SDLC (System Development Life Cycle). The visualization of the application made by Blender 2.69 using 3D objects. This application adds to the user experience more with 90.31% index points of total maximum of 100% which indicates that the application is easy to use and easy to be learned, This application works optimally if the light in a location that has a minimal emission of 3 Lux to 6 Lux for outdoor and indoor.